واقع الأوضاع الديمغرافية والاجتماعية لقطاع غزة قبل طوفان الأقصى - مشنان، فوزى (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2024)
تهدف ورقتنا البحثية للتعرف على واقع الأوضاع الديمغرافية والاجتماعية الصعبة التي ميزت قطاع غزة خلال السنوات الأخيرة وخلال حكم حماس للقطاع وقبل قيام طوفان الأقصى، وما نتج عنها من آثار سلبية على القطاع وسكانه بسبب الحصار الذي فرضه الاحتلال الصهيوني عليه وعلى سكانه. ومن بين أهم النتائج التي تم التوصل إليها كون قطاع غزة شهد أوضاعا ديمغرافية واجتماعية وصحية انعكست سلبا على القطاع وسكانه بسبب رئيسي وهو فرض الحصار والضغط المادي والنفسي على سكانه والهدف مكشوف ومفضوح وهو القضاء على منظمة حماس عدوها اللدود الذي لقنها درسا لن ينسى مستقبلا بقيامه بعملية طوفان الأقصى المباركة والتي تعتبر كرد طبيعي على الظلم والعدوان الصهيوني وتعديه على مقدرات ومقدسات الشعب الفلسطيني. Our research paper aims to identify the reality of the difficult demographic and social conditions that characterized the Gaza Strip during recent years, during Hamas’ rule of the Strip and before the Al-Aqsa flood, and the resulting negative effects on the Strip and its residents due to the siege imposed by the Zionist occupation on it and its residents. Among the most important results reached is that the Gaza Strip witnessed demographic, social, and health conditions that negatively affected the Strip and its residents due to the main reason, which was the imposition of the siege and the physical and psychological pressure on its residents. The goal was exposed and exposed, which was to eliminate the Hamas organization, its arch enemy, which taught it a lesson that will not be forgotten in the future by carrying out Operation Flood. Blessed Al-Aqsa, which is considered a natural response to Zionist injustice and aggression and its infringement on the capabilities and sanctities of the Palestinian people.
Keywords: الأوضاع الصحية -- الاحتلال الصهيوني -- حركة حماس -- فلسطين